PENGARUH KONSENTRASI DAN INTERVAL WAKTU PEMBERIAN PUPUK ORGANIK CAIR AZOLLA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCOY Varietas Nauli (Brassica rapa chinensis L.) - Syaifuddin, Muhammad; Puspitorini, Palupi (Universitas Islam Balitar, 2023)
The aim of the research was to determine whether there was a real interaction effect of Azolla POC concentration and the time interval of POC administration on the yield and growth of Pakcoy plants. The research used a Randomized Group Design (RAK) arranged factorially including 2 factors which were repeated 3 times. Factor I is the nutrient dose of Azolla liquid organic fertilizer which consists of 3 levels 4 namely D1: 0 ml/1 water, D1: 2 ml/l water, D2: 4 ml/l water, D3: 6ml/l water and Factor II is Time interval for application of 3 level Azolla liquid organic fertilizer. S1: Application time interval 2 days, S2: Application time interval 4 days, S3: Application time interval 6 days. Plant height (cm) was observed at 0, 7, 14, 21, 28, 35 HST, measured using a meter. The number of leaves at 1, 3, 5, 7 and 9 WAP and leaf width at 0, 7, 14, 21, 28, 35 HST were measured using a tape measure. Accumulated fruit weight per plant (grams) The wet fruit weight of Pokcoy plants is determined by weighing all parts of the plant (roots, stems, leaves). Plants were weighed one by one using an analytical balance. Observational data were analyzed using Analysis of Variance (ANOVA) with a level of α = 0.05 and if there were significant differences between treatments then a further test was carried out using the DMRT test (Duncan's Multiple Range Test) at a level of α = 0.05. The results of research that have been carried out have concluded that there is a real interaction between the concentration of Azolla liquid organic fertilizer (D) and the time interval for POC application on the growth and yield of Pak Choy plants. The best treatment combination for plant height variables; number of leaves; leaf area is the D2S2 treatment, namely the combination treatment of azolla POC concentration of 4 ml/L and the POC application time interval of 4 days, while for plant fresh weight the best combination is D2S3, namely the combination treatment of 6 ml Azolla POC concentration and 4 day POC application time interval with weight. fresh plants amounting to 58.17 grams.